Spectrophotometric Change of Butterfly Pea (Clitoria ternatea L.) Flower Extract in Various Metal Ion Solutions During Storage - Abdullah Muzi Marpaung; Dania Pustikarini (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This study aimed to investigate the effect of six chloride salts on butterfly pea flower extract’s anthocyanins stability. The salts were NaCl, KCl, CaCl2, MgCl2, FeCl3, and AlCl3. The samples were analyzed using a UV-Vis spectrophotometer to observe color degradation and change in hue during storage. The extraction of anthocyanins was done using a modified method, and the solutions were stored in dark vials at room temperature. The degradation kinetics of benzene derivatives, acyl groups, non-anthocyanin flavonoid, flavylium cation, quinonoidal base and anionic quinonoidal base were evaluated using the first-order reaction, and the half-life was calculated. The effect of metal ions was studied by analyzing the change in absorbance of each band using regression analysis and a slope test. The results showed that monovalent (Na+ and K+) and divalent (Ca2+ and Mg2+) ions did not result in a significant shift in the spectrogram. Trivalent metal ions (Al3+ and Fe3+) had limited interaction with the anthocyanins, heightened the brown color, and decreased the overall color quality. K+, Ca2+, Mg2+, Al3+, and Fe3+ ions showed the ability to improve the stability of the extract’s color, while Na+ tended to accelerate color degradation. The pattern of changes in the spectrogram during storage suggests that color degradation occurs in two ways: the unfolding of hydrophobic interactions and the deacylation of anthocyanin. Trivalent metal ions showed the best stability performance, with Fe3+ preventing the unfolding of hydrophobic interactions and Al3+ hindering the deacylation. The combination of the two is highly likely to improve the color stability of the butterfly pea flower extract. However, both increase the browning index, thus decreasing color quality. This research highlights the potential of adding cations to improve the color stability of the butterfly pea flower extract, making it a more attractive food coloring agent.